Surface Roughness Evaluation Of Experimental Dental Nanocomposite After Bleaching - Mohamad, Dasmawati; Ab Ghani, Zuryati; Ooi, Qian Qian; Mohammed Ali, Zaid Hameed (2011)

(untitled)
Bleaching or tooth whitening is getting more popular in this world that concerns esthetic [1].